Numerical Simulation of Dam-Break Flood Impacting Buildings by a Volume of Fluid and Immersed Boundary Method - Yu, Chinghao; Li, Yulong; Meng, Wenkang; An, Ruidong (Frontiers in Earth Science, 2020)
A three-dimensional hydrodynamic model is developed to study the propagation of dam-break-induced flood and the interaction between floods and buildings. In the proposed mathematic model, the volume of fluid (VOF) method and the immersed boundary (IB) method are used to address the air/water interface and fluid/structure interface respectively. Barely a limited number of publications focus on 3D simulations of the dam-break flood impacting buildings in the long flume heretofore, for researching the dam-break flood impacting buildings involves some hard issues like a wave breaking phenomena, flood-building interaction, and computational efficiency. Therefore, the highlights to this paper are: (1) The THINC/SW (THINC with Slope Weighting), which is extremely simple and efficient and meanwhile can also solve the wave breaking process, is adopted in the paper. Furthermore, its numerical accuracy is comparable to the conventional VOF schemes that use geometrical reconstructions. (2) The direct forcing IB method, which can be easily applied to three-dimensional simulation, is adopted to promote the computational efficiency of the three-dimensional numerical model and handle flood-building interaction interface treatment. The proposed VOF/IB model is validated by the physical experiment results and is also compared with the two-dimensional depth-averaged Shallow-Water Equations (SWEs), and Coupled Level Set/Volume of Fluid and Immersed Boundary (CLSVOF/IB) models in terms of accuracy and efficiency.